2016
DOI: 10.1186/s12985-016-0533-3
|View full text |Cite
|
Sign up to set email alerts
|

Occult Hepatitis B virus infection in previously screened, blood donors in Ile-Ife, Nigeria: implications for blood transfusion and stem cell transplantation

Abstract: BackgroundHepatitis B virus (HBV) transmission through blood transfusion is reduced by screening for hepatitis B surface antigen (HBsAg). However this method cannot detect the presence of occult hepatitis B virus infection. This study sought to determine the prevalence of occult hepatitis B virus infection among blood donors in Ile-Ife, Nigeria. For the first time in Nigeria we employed an automated real-time PCR- method to investigate the prevalence of occult HBV in blood donors.MethodsBlood donors screened w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 73 publications
7
21
0
Order By: Relevance
“…In recent years, several studies on the infectivity of OBI donors via blood transfusion were reported [10][11][12][13][14]. In Italy, two cases of posttransfusion hepatitis were found in which the sequence identity of donor-recipient by phylogenetic analysis was confirmed [16].…”
Section: Mechanism and Infectivity Of Occult Hepatitis B Infections Imentioning
confidence: 96%
See 3 more Smart Citations
“…In recent years, several studies on the infectivity of OBI donors via blood transfusion were reported [10][11][12][13][14]. In Italy, two cases of posttransfusion hepatitis were found in which the sequence identity of donor-recipient by phylogenetic analysis was confirmed [16].…”
Section: Mechanism and Infectivity Of Occult Hepatitis B Infections Imentioning
confidence: 96%
“…Nevertheless, HBV continues to be the most common posttransfusion infection because the residual risk is not limited to pre-seroconversion window period, but it extends to donors with OBI [6,[10][11][12][13][14]. These donors do not exhibit significant levels of HBs-Ag in the serum, with fluctuating low levels of viremia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among blood donors in recent years, the incidence of OBI has varied with the prevalence of HBV and public health conditions. Specifically, the OBI incidence was 1:27 (19 of 507 donors) in Nigeria, 1:450 (8 of 3600 donors) in the Brazilian Amazon, 1:2450 (163 of 399,326 donors) and 1:3239 (95 of 307,740 donors) at the Hong Kong Red Cross Blood Transfusion Service and Shenzhen Blood Center of South China, 1:19,130 (23 to 4.4 million donors) in the Netherlands, 1:14,903 (34 of 506,689 donors) in Spain, at least 1:2200 (548 of 1,205,796 donors) in a multicenter investigation in China, and 1:5045 (298 of 1,503,484 donors) in a worldwide, multicenter investigation . A recent survey conducted by the National Institute of Diagnostics and Vaccine Development in Infectious Diseases of China showed that the incidence of OBI in blood donors in South China was 1:631 (61 of 38,499 donors), and more than one‐half (34 of 61 donors) of the OBI blood samples harbored major hydrophilic region (MHR) mutations, which are associated with failure to detect HBsAg .…”
mentioning
confidence: 99%